THE ANALYSIS OF ASSESSMENT ITEMS TEST OF MATH SUBJECT IN MIDTERM ON ODD SEMESTER OF XI IPS 2 CLASS STUDENTS AT SMA - Lisa Octaviani; Anggit Prabowo (Universitas Ahmad Dahlan, 2019)
The test instrument for the odd midterm assessment questions in the XI grade of the social science class of mathematics subjects has not yet been analyzed for its characteristics. Therefore, this study aims to analyze the characteristics of midterm assessment items of the mathematic subject in State Senior High School (SMA Negeri) 1 Ngaglik. The research is a research with post facto with a quantitative descriptive approach with subjects, namely the instrument items for midterm assessment questions in the form of open questions as many as five questions. The research object is a twentieth grade in SMA Negeri 1 Ngaglik that consists of 32 students. An analyzing data used Microsoft excel on manually of validity, power difference difficulty index, and reliability. The result showed that: 1) midterm test instrument of mathematics subjects are categorized very high, which means the items are valid with a V-Aiken index value of 1 for each; 2) from 5 questions, the difficulty index obtained was one which was categorized as an easy question and four moderate questions; 3) from 5 questions, two questions have good power difference category, and three questions were categorized sufficient; 4) the reliability obtained was 0,501 which was categorized as medium.